Выбор метода анестезии при проведении экстренного кесарева сечения - Ткачуковский, А.Ф.; Иванченко, Л.А.; Курган, А.И. (Таврический медико-биологический вестник, 2011)
Враховуючи показання до ургентного кесаревого розтину, класифікацію кесаревого розтину за
ступенем ургентностI показань, показання та протипоказання щодо того чи іншого методу анестезії,
ми вивели чіткі критерії для вибору методу анестезії при ургентному кесаревому розтині. Considering indications to emergency Cesarean section, classification of Cesarean section by degree of
promptness of indications, indications and contraindications to this or that method of anesthesia. We have
deduced accurate criteria for a choice of a method of anesthesia at emergency Cesarean section.